Subtitles in the 2020s: The Influence of Machine Translation - Hagström, Hanna; Pedersen, Jan (Journal of Audiovisual Translation, 2022)
Machine translation is now making serious inroads into the field of interlingual subtitling. This has been made possible by the use of template files and higher reading speeds. As we move into this new phase in the development of the subtitling process, the phase of machine-translated and postedited subtitles, it is highly pertinent to look at marks that this new process leaves on the subtitled product, i.e., the subtitles themselves. We conducted a diachronic study of subtitles before and after machine translation was part of the process. We did this by comparing a corpus of Swedish subtitles of Anglophone TV programmes produced after machine translation was introduced to a corpus of subtitles from before that period. We also took data from studies of earlier processes into account. When assessed using existing guidelines and the FAR model, the post-edited subtitles produced in the 2020s were found to be faster, more oral, less cohesive, less complete and with less meticulous punctation and line-breaks than those produced in the 2010s. They were also of significantly lower quality in all areas investigated. Based on these results, we suggest that more research and development is needed to raise quality levels, and to make professional subtitlers augmented translators. Lay summary Machine translation is now starting to be used for subtitling from one language into another. This has been made possible by the use of higher reading speeds and recent technical innovations that simplify and automatise the process. As we move into this new phase in the development of the subtitling process, the phase of machine-translated subtitles which are then post-edited by humans, it is time to look at what marks this new process leaves on the subtitles themselves. We conducted a study of subtitles made before and after machine translation was part of the process. We did this by comparing Swedish subtitles of English-language TV programmes produced after machine translation was introduced, to subtitles from before that period. We also took data from studies of earlier processes into account. The results show that the post-edited subtitles produced in the 2020s were found to be faster, more oral, less cohesive, less complete and with less meticulous punctation and line-breaks than those produced in the 2010s. They were also of significantly lower quality in all areas investigated. Based on these results, we suggest that more research and development is needed to raise quality levels, and to put professional subtitlers in charge of the process.